Tailoring the physical and chemical properties of Sn1-xCoxO2 nanoparticles: an experimental and theoretical approach - Aragon, F. F. H.; Villegas-Lelovsky, L. [UNESP]; Cabral, L.; Lima, M. P.; Aquino, J. C. R.; Mathpal, M. C.; Coaquira, J. A. H.; Silva, S. W. da; Nagamine, L. C. C. M.; Parreiras, S. O.; Gastelois, P. L.; Marques, G. E.; et al. (Royal Soc Chemistry, 2020)
In this work, we present a coupled experimental and theoretical first-principles investigation on one of the more promising oxide-diluted magnetic semiconductors, the Sn1-xCoxO2 nanoparticle system, in order to see the effect of cobalt doping on the physical and chemical properties. Our findings suggest that progressive surface enrichment with dopant ions plays an essential role in the monotonous quenching of the surface disorder modes. That weakening is associated with the passivation of the oxygen vacancies as the Co excess at the surface becomes larger. Room-temperature Sn-119 Mossbauer spectroscopy data analysis revealed the occurrence of a distribution of isomer shifts, related to the different non-equivalent surroundings of Sn4+ ions and the coexistence of Sn2+/Sn4+ at the particle surfaces provoked by the inhomogeneous distribution of Co ions, in agreement with the X-ray photoelectron spectroscopy measurements. Magnetic measurements revealed a paramagnetic behavior of the Co ions dispersed in the rutile-type matrix with antiferromagnetic correlations, which become stronger as the Co content is increased. Theoretical calculations show that a defect with two Co mediated by a nearby oxygen vacancy is the most likely defect. The predicted effects of this defect complex are in accordance with the experimental results.